Silencing of the Wheat Protein Phosphatase 2A Catalytic Subunit TaPP2Ac Enhances Host Resistance to the Necrotrophic Pathogen Rhizoctonia cerealis - Zhu, Xiuliang; Wang, Yuanyuan; Su, Zhenqi; Lv, Liangjie; Zhang, Zengyan (Frontiers in Plant Science, 2018)
Eukaryotic type 2A protein phosphatases (PP2A) are consisted of a scaffold subunit A, a regulatory subunit B, and a catalytic subunit C. Little is known about the roles of PP2Ac proteins involved in plant responses to necrotrophic fungal pathogens. Sharp eyespot, caused by the necrotrophic fungus Rhizoctonia cerealis, is a destructive disease of wheat (Triticum aestivum), an important staple food crop. Here, we isolated TaPP2Ac-4D in wheat, which encodes a catalytic subunit of the heterotrimeric PP2A, and characterized its properties and role in plant defense response to R. cerealis. Based on sequence alignment of TaPP2Ac-4D with the draft sequences of wheat chromosomes from the International Wheat Genome Sequencing Consortium (IWGSC), TaPP2Ac-4D gene is located on the long arm of wheat chromosome 4D and has two homologs assigned on wheat chromosomes 4A and 4B, respectively. Sequence and phylogenetic tree analyses revealed that the TaPP2Ac protein is a typical member of the PP2Ac family and belongs to the subfamily II. TaPP2Ac-4B and TaPP2Ac-4D displayed higher transcriptional levels in R. cerealis-susceptible wheat cultivar Wenmai 6 than in the resistant wheat line CI12633. The transcriptional levels of TaPP2Ac-4B and TaPP2Ac-4D were significantly elevated in wheat R. cerealis after infection and upon H2O2 treatment. Virus-induced gene silencing results revealed that the transcriptional knockdown of TaPP2Ac-4D and TaPP2Ac-4B significantly increased wheat resistance to R. cerealis infection. Meanwhile, the transcriptional levels of certain pathogenesis-related (PR) and reactive oxygen species (ROS)-scavenging enzyme encoding genes were increased in TaPP2Ac-silenced wheat plants. These results suggest that TaPP2Ac-4B and TaPP2Ac-4D negatively regulate defense response to R. cerealis infection possibly through modulation of the expression of certain PR and ROS-scavenging enzyme genes in wheat. This study reveals a novel function of the plant PP2Ac genes in plant immunity responses.